군집 드론 네트워크를 위한 임무 중요도 기반 메시지 전송 기법 - 곽욱수 (The Graduate School, Ajou University, 2024)
무인 항공기(Unmanned Aerial Vehicle, UAV)를 효율적으로 사용하기 위해 서는 다수의 무인 항공기를 동시에 운용할 수 있는 시스템이 필요하며 다중 무 인 항공기를 사용하는 시스템에서는 무인 항공기 간 충돌을 방지할 수 있어야 원활한 시스템 운용이 가능하다. 무인 항공기들을 직접 조종하여 충돌을 방지 하는 방식은 운용 무인 항공기의 수량이나 비행 궤도 복잡도가 증가한다면 충 돌 발생 확률도 증가하게 된다. 또한 무인 항공기 제어자가 무인 항공기 상황 을 시각적으로 확인할 수 있어야 하는 제약도 존재한다. 따라서 효율적이고 안 전한 다중 무인 항공기 운용을 위해 능동적인 충돌 방지 기능의 필요성이 존재 한다. 또한 충돌 방지를 위해 무인 항공기 간 메세지 통신이 원활히 이루어질 수 있어야 한다. 이때 각 무인 항공기의 임무를 고려한 메시지 전송 기법이 필 요하다. 본 연구에서는 원거리 상황 다중 무인 항공기 운용 시 충돌 방지를 위 하여 공중 환경을 반영한 거리 기반 편대 비행 방식 군집 무인 항공기 시스템 을 제안 및 시뮬레이션을 통한 구현과 검증을 목표로 잡는다. 키워드 : 공중, 임무 기반, 편대 비행, 무인 항공기, 멀티 홉 통신, 다중 무인 항공기 서비스|In order to use unmanned aerial vehicles (UAVs) efficiently, a system that can operate multiple UAVs simultaneously is required, and in a system that uses multiple UAVs, it is necessary to prevent collisions between UAVs for smooth system operation. The method of preventing collisions by directly controlling UAVs increases the probability of collisions as the number of operational UAVs or the complexity of flight trajectories increases. There is also the constraint that the drone controller must be able to visually check the drone situation. Therefore, there is a need for active collision avoidance for efficient and safe multi-UAV operation. In addition, message communication between drones must be seamless for collision avoidance. This requires a message transmission technique that considers the mission of each drone. In this study, we propose a distance-based formation flight method swarming unmanned aircraft system that reflects the aerial environment for collision prevention when operating multiple unmanned aircraft in a long-distance situation, and aim to implement and verify it through simulation.
학위논문(석사)--AI융합네트워크학과,2024. 2
Keywords: 공중; 다중 무인 항공기 서비스; 멀티 홉 통신; 무인 항공기; 임무 기반; 편대 비행